Children Victims of Parental Substance Abuse and Future Incarceration - Hughes, Jennifer; Cooper, Jaedn; Rios, Samantha (Kansas State University. Dept. of Sociology, Anthropology and Social Work, 2020)
The purpose of this mixed-method design study is to discover if the Adverse Childhood Experience(ACE) of having (a) parent(s) with a substance abuse issues effects the likelihood of the child being incarcerated in their future. In background research, we found that it is very common for abusive parents or other ACE to affect the child’s success, especially within their own future family violence and their presence in the criminal justice system. This study will survey approximately 100 inmates in the Topeka Correctional Facility and 100people in the Topeka, Kansas area who have never been incarcerated or arrested. The self-administered paper survey will ask questions about the individual’s parents are their parents use of substances when they were children and being incarcerates as an adult. The average score between the inmate group and the non-criminal group will be compared to see if there was a difference in their parent’s substance use severity in their childhoods.Finding these results is significant because it will show us a correlation between parental substance abuse and the link it has to their children’s future involvement in the criminal justice system (Correctional facilities).It also provides us with more specific information in relation to parental substance abuse and its effects on the child who falls victim and their future. If we find that this is a common issue and trend that parental substance abuse raises the likelihood of future incarceration for the child, we can also begin researching ways to combat this social issue.
Kirmser Undergraduate Research Award - Group category, honorable mention
Keywords: Adverse Childhood Experience; Substance Abuse; Abusive Parents; Topeka (KS) Correctional Facility; Incarceration